A trajetória intelectual de Benedicto Silva: tecnocracia, ideologia e capitalismo no Brasil (1930-1964) - Meirelles, Alexandre de Paula (2021)
With Getúlio Vargas' rise to power in the 1930s, the Brazilian state became committed to the demands of the industrial class in order to organise the fundaments that would accelerate the industrialisation process through state coordination and concentration of power, along corporatist lines. In this process, to organise this mission with the government, a managerial class, which has a legal and ideological superstructure that differs from the traditional bourgeoisie and proletariat gains a central rule. Thinking the state apparatus in terms of the collective appropriation of surplus value and installed in the heart of the state, the managers began a process of reorganization of the state structures while also organizing themselves to expand their class through an exchange process in the United States, where they had contact with the modern management and organizational techniques of Scientific Administration. Benedicto Silva, an intellectual from Goiás who worked for the Administrative Department of the Public Service (DASP), was a key figure in this process that articulated the training of Brazilian civil servants with international organizations connected to the United Nations (UN) to ensure the reproducibility of managers with the aim of occupying strategic positions in public and private service with the industrial acceleration of Brazil and Latin America. Through the analysis of Benedicto Silva's intellectual and institutional trajectory, we intend to understand the nuances of the ideology of the managers and then demonstrate how the managerial class, organized within the Vargas state, designed its reproduction and increased the influence of its class in Brazil and Latin America with the foundation of the Brazilian School of Public Administration (EBAP) within the Getúlio Vargas Foundation.